Comparative assessment of the immunogenicity of various revaccination regimens against the SARS-CoV-2 - O. M. Drapkina; S. A. Berns; A. Yu. Gorshkov; L. N. Ryzhakova; O. V. Zhdanova; M. G. Chaschin; O. A. Litinskaya; A. A. Savicheva; M. S. Pokrovskaya (Кардиоваскулярная терапия и профилактика, 2023)
Along with efficacy and safety, it is extremely important to study the severity of humoral and cellular immunity during not only vaccination, but also revaccination against the Severe Acute Respiratory Syndromerelated CoronaVirus 2 (SARS-CoV-2).Aim. To compare the immunogenicity (humoral and cellular immunity) of various (heterologous and homologous) revaccination regimens against coronavirus disease 2019 (COVID-19) in a prospective observational study.Material and methods. In individuals aged ≥18 years, in the absence of contraindications to vaccination, two following types of vaccines were used for primary vaccination and revaccination: Gam-COVIDVac and CoviVac. Group I patients received Gam-COVID-Vac at each stage of primary and secondary vaccination; patients of group II — Gam-COVID-Vac at each stage of primary vaccination, CoviVac at each stage of re-vaccination; patients of group III — CoviVac at each stage of primary vaccination and Gam-COVID-Vac at each stage of revaccination; patients of group IV — CoviVac at each stage of primary and secondary vaccination. All participants (at each stage of vaccination, revaccination and 12 months after the primary vaccination) were determined the level of IgG to the receptor-binding domain of SARS-CoV-2 spike (S) protein and T-cell immunity to SARSCoV-2.Results. The maximum level of IgG at the second stage of revaccination was observed in groups I and III. In addition, in groups I, III and IV, a significant (p<0,0001) increase in IgG level by the second stage of revaccination was noted, the most pronounced in group III. In addition, there was a significantly (p<0,05) higher level of IgG at I and II stages of revaccination (Visit 3 and 4) among those vaccinated with Gam-COVID-Vac — 520 and 540 BAU/ml, respectively, compared with group IV vaccinated with CoviVac — 467 and 478 BAU/ml, respectively. The maximum and significant increase in active T-cells by the second stage of revaccination (Visit 4) was noted in groups I (p<0,0001) and III (p<0,0022) of vaccinated individuals, where it amounted to 11 and 12, respectively, which allows to consider the result positive (>8). At the same time, the level of active T cells responding to SARS-CoV-2 nucleocapsid Ag stimulation by Visit 4 (stage II of revaccination) was noted in groups II (14,5) and IV (12).Conclusion. The use of the Gam-COVID-Vac vaccine as a booster dose in both homologous and heterologous vaccination regimens against the SARS-CoV-2 virus is most effective for stimulation and humoral and T-cell post-vaccination response.